Fire-triggered flowering is the dominant post-fire strategy in a tropical savanna - L. Zirondi, Heloiza [UNESP] (2021)
Questions: In fire-prone ecosystems, fire can enhance the flowering and fruiting of many species, a strategy assumed to be well represented in savanna. Despite this, there are surprisingly few studies assessing how prevalent fire-stimulated flowering is. Thus, we asked: (a) are there differences in the reproductive phenology of Cerrado plants between recently burned and unburned areas; (b) how does fire affect the speed of flowering and how does this differ between growth forms; and (c) what are the post-fire flowering (PFF) strategies of Cerrado species and is there evidence for high proportions of obligate PFF?. Location: Open savannas (campo sujo in the Cerrado) in Central Brazil (Reserva Natural Serra do Tombador — RNST, 13°35–13°38' S and 47°45'–47°51' W). Methods: We established six plots, three recently and frequently burned (FB) and three excluded from fire for six years (E). In all treatments, the number of species flowering and fruiting was counted every 15 days for three months, and then at six, nine and 12 months after fire. We also counted the number of reproductive and vegetative shoots in 10 subplots (1 m × 1 m) per plot. Results: Approximately 66% of species studied were fire-stimulated, with half of these only flowering after fire (obligate PFF). Fire-enhanced flowering was rapid, with the clearest differences between burned and unburned plots seen in the first 30 days, and up to three months after fire, where there were up to two times more species flowering in the FB than E areas. Conclusions: The extremely high proportion of PFF species, at least five times that reported for heathlands and other shrub communities, highlights the role that short-interval fire regimes have in savanna ecosystems, selecting for resprouting life forms and PFF dominance, particularly in herbaceous species. Rapid post-fire reproduction may be a strategy to disperse large quantities of seed into an environment with a small recruitment window.